IMPLEMENTASI MANAGEMENT SECURITY SEBAGAI PENGARUH K3 DAN EFEK BEBAN KERJA YANG BERBASIS NILAI KEBANGSAAN UUD 1945 DI PT. YAMAHA MUSIC MANUFACTURING INDONESIA (YMMI) - Andika Prastiyo Wibowo; Edy Soesanto, Muhamad Fadel Taufik (ADISAM PUBLISHER, 2024)
This study discusses the influence of Occupational Health and Safety (K3) and Workload on the Security Management System at PT Yamaha Music Manufacturing Indonesia. Through qualitative analysis with in-depth interviews, this research highlights the importance of good K3 implementation in increasing the effectiveness of a company's security management system. A safe and healthy work environment was found to have a positive impact on employee productivity and reduced risk of work accidents. Apart from that, this study also found that excessive workload can disrupt employee efficiency and affect awareness of work safety practices.The legal basis for Occupational Safety and Health (K3) begins with the 1945 Constitutions (UUD 1945) Article 27 paragraph (2). The influence of K3 and workload on the security management system was found to be simultaneous, emphasizing the need for good management of these two factors to strengthen the success of the company's security management system.